Observations of light-induced structural changes of retinal within rhodopsin. - Gröbner, G; Burnett, I; Glaubitz, C; Choi, G; Mason, A; Watts, A (2000)
Photo-isomerization of the 11-cis retinal chromophore activates the mammalian light-receptor rhodopsin, a representative member of a major superfamily of transmembrane G-protein-coupled receptor proteins (GPCRs) responsible for many cell signal communication pathways. Although low-resolution (5 A) electron microscopy studies confirm a seven transmembrane helix bundle as a principal structural component of rhodopsin, the structure of the retinal within this helical bundle is not known in detail. Such information is essential for any theoretical or functional understanding of one of the fastest occurring photoactivation processes in nature, as well as the general mechanism behind GPCR activation. Here we determine the three-dimensional structure of 11-cis retinal bound to bovine rhodopsin in the ground state at atomic level using a new high-resolution solid-state NMR method. Significant structural changes are observed in the retinal following activation by light to the photo-activated M(I) state of rhodopsin giving the all-trans isomer of the chromophore. These changes are linked directly to the activation of the receptor, providing an insight into the activation mechanism of this class of receptors at a molecular level.